THE INFLUENCE OF GOOD GOVERNANCE AND INTERNAL CONTROL ON THE PERCEPTION OF FINANCIAL MANAGEMENT PERFORMANCE AT THE OFFICE OF THE REGIONAL FINANCIAL MANAGEMENT AGENCY (BPKD) DKI JAKARTA PROVINCE - Karina Anjasmara; Kumba Digdowiseiso (SEAN Institute, 2023)
This study aims to determine how much influence good governance and internal control have on the perception of financial managers performance at the Regional Financial Management Agency (BPKD) Office of DKI Jakarta Province. In this study, a sample / population of 100 respondents was used with the method used is a simple random sampling method. Descriptive analysis and multiple linear regression analysis are data analysis techniques used in this study with the STATA Statistics version 16 program. Based on the results of this study, it was found that variables of good governance and internal control are very influential in financial management at the Office of the Regional Financial Management Agency (BPKD) of DKI Jakarta Province.